Subclinical thyroid dysfunction in the first trimester of pregnancy: 'Disease' versus physiological (pulsatile) variation in TSH concentrations. (16th June 2020) - Lewandowski, Krzysztof C.; Garnysz, Karolina; Horzelski, Wojciech; Kawalec, Joanna; Budzen, Karolina; Grzesiak, Mariusz; Lewinski, Andrzej
Abstract: Background: There is no universal consensus regarding cut‐off points for TSH in pregnancy, so concentrations of 2.5 or 4.0 mIU/L were suggested for first trimester (Endocrine Society [2012] and ATA [2017] guidelines, respectively). Yet, the impact of physiological variation in TSH secretion has not been assessed. Subjects and Methods: We assessed baseline concentrations of free T4, free T3 and TSH at 30‐minute intervals (between 7.00 and 9.00 hours) in 110 healthy pregnant women, age 30.2 ± 6.0 years, 9.9 ± 2.4 weeks of gestation, and in 19 female controls, age 28.9 ± 10.7. Results: Mean TSH concentrations in pregnant women were 1.62 ± 1.26 mIU/L and on average varied by 39.5% (dispersion between the highest and the lowest TSH), with no difference in TSH variation between pregnant women and controls. Taking into account the highest TSH out of five consecutive measurements, TSH >2.5 mIU/L and TSH above 4.0 mIU/L were found in 23 (20.9%) and 10 (9.1%) pregnant women, respectively. In contrast, when the lowest TSH value was considered, then concentrations of TSH >2.5 mIU/L and >4.0 mIU/L were found in 14 (12.7%) and 4 (3.6%) women, respectively. This discrepancy was even more pronounced in aTPO‐negative subjects (21 [21.2%] vs 8 [8.1%] women, for TSH >2.5 mIU/L, and six [6.06%] vs one [1.01%], for TSH >4.0 mIU/L). Furthermore, either six (5.4%) or 10 (9.1%) women had TSH concentrations below 0.1 mIU/L. Conclusions: In a significant number of patients, diagnosis of subclinical thyroid dysfunction could be erroneously made not as a result of 'disease', but as a result of physiological variation in TSH concentrations.